UniSPACES - APPLICATION FOR MANAGING ROOM AND LABORATORY RESERVATIONS (CIPEEX, 2024)
UniSpaces is an innovative solution in the form of a mobile application that aims torevolutionize the management of academic spaces, such as classrooms and laboratories, inboth public and private educational institutions. This software was developed with the intentionof significantly improving the administration of these environments, providing a comprehensiveapproach to optimization and control. The main objective of UniSpaces is to simplify andimprove the allocation of classrooms and laboratories, making this process more efficient andtransparent. With the help of this platform, schools and colleges can allocate resources moreintelligently, avoiding scheduling conflicts and maximizing the use of available spaces. Thisnot only improves the organization of academic activities, but also contributes to reducingoperational costs. Accessibility via mobile devices is another key feature of UniSpaces. Thismeans that managers and those responsible for space allocation can access and updateinformation in real time, from anywhere, facilitating agile and informed decision-making.Therefore, UniSpaces is a comprehensive platform that aims to improve academic spacemanagement in all aspects. Focusing on efficient space allocation, equipment control,organization, management efficiency and security, this solution offers an improved experiencefor both managers and users. Its intuitive, responsive, stable and secure approach makes itan indispensable ally for educational institutions seeking to improve their academicmanagement processes.
Keywords: Academic management; Reservations; Resources; Efficiency